2011
DOI: 10.1371/journal.pone.0018691
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Tyrosine Kinase Inhibitors Activate Autophagy as a Cytoprotective Response in Human Lung Cancer Cells

Abstract: Epidermal growth factor receptor tyrosine kinase inhibitors gefitinib and erlotinib have been widely used in patients with non-small-cell lung cancer. Unfortunately, the efficacy of EGFR-TKIs is limited because of natural and acquired resistance. As a novel cytoprotective mechanism for tumor cell to survive under unfavorable conditions, autophagy has been proposed to play a role in drug resistance of tumor cells. Whether autophagy can be activated by gefitinib or erlotinib and thereby impair the sensitivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
202
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 225 publications
(213 citation statements)
references
References 35 publications
11
202
0
Order By: Relevance
“…Meanwhile, blocking autophagy with either the lysosomal inhibitor chloroquine or ATG7 siRNAs strongly enhances the apoptosis induced by various anticancer agents such as tyrosine kinase inhibitors. [20][21][22][23] SQSTM1, a member of the autophagic receptors that promote autophagy activation, is highly expressed in many human cancers. [24][25][26] In addition, accumulation of SQSTM1 promotes tumorigenesis while inhibition of autophagy prevents tumor growth in nude mice.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, blocking autophagy with either the lysosomal inhibitor chloroquine or ATG7 siRNAs strongly enhances the apoptosis induced by various anticancer agents such as tyrosine kinase inhibitors. [20][21][22][23] SQSTM1, a member of the autophagic receptors that promote autophagy activation, is highly expressed in many human cancers. [24][25][26] In addition, accumulation of SQSTM1 promotes tumorigenesis while inhibition of autophagy prevents tumor growth in nude mice.…”
Section: Introductionmentioning
confidence: 99%
“…EGFR targeted therapy has been characterised as a potent autophagy-inducing stimulus in cancer cells 17,19,42,44,45,[48][49][50] Interestingly, we found that all CRC cell lines utilised in this work exhibit basal autophagic flux irrespective of their PI3K or KRAS mutational status. Although earlier studies have suggested that autophagy can be regulated in an mTORC1-independent manner, [13][14][15][16][17][18][19] the role of basal autophagy in cancer remains elusive.…”
Section: Discussionmentioning
confidence: 85%
“…It has been proposed by us and others that in established tumours autophagy plays a pro-survival role, 28,39,41,42,45,46,57 in particular upon starvation or downstream inhibition of oncogenic kinase signalling, both of which result in inhibition of the main autophagy inhibitor, the PI3K/AKT/mTORC1 pathway. However, little is known on the role of autophagy and autophagy-like pathways in the presence of active PI3K/AKT/mTORC1 signalling in cancer cells, due to mutations in either PI3K or RAS pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations